KEBIJAKAN SISTEM ZONASI DALAM PERSPEKTIF PENDIDIKAN - Gunarti Ika Pradewi; Rukiyati Rukiyati (Universitas Negeri Malang, 2019)
Abstract: The purpose of this study was to find out about school attendance zones system policies in the educational perspective in Indonesia. This is a qualitative research using phenomenology method. The perspective in this study is the perspective of teachers and principals from a favorite and unfavorite school. The results of the study show the perspectives of the teachers and principals about school attendance zones are: (1) facilitating access to education services; (2) equalizing school quality; (3) reducing school quality; (4) it is not suitable at high school level; ( 5) restricting students from choosing schools; (6) zoning policies must be accompanied by equal distribution of educational facilities and infrastructure; and (7) damaging diversity. Abstrak: Tujuan dari penelitian ini ialah untuk mengetahui tentang kebijakan sistem zonasi dalam perspektif pendidikan di Indonesia. Penelitian dilakukan dengan menggunakan pendekatan kualitatif, metode fenomenologi. Perspektif yang diangkat ialah perspektif guru dan kepala sekolah dari SMA favorit dan tidak favorit. Hasil penelitian menunjukkan perspektif para guru dan kepala sekolah tentang zonasi meliputi: (1) zonasi memudahkan akses layanan pendidikan; (2) zonasi memeratakan kualitas sekolah; (3) zonasi menurunkan kualitas sekolah; (4) zonasi tidak cocok ditetapkan di tingkat SMA; (5) sistem zonasi membatasi siswa memilih sekolah; (6) kebijakan zonasi harus disertai pemerataan sarana dan prasarana pendidikan; dan (7) zonasi merusak kebhinekaan.